Early marriage and early childbearing in South Asia: trends, inequalities, and drivers from 2005 to 2018. Issue 1 (1st December 2020) - Scott, Samuel; Nguyen, Phuong Hong; Neupane, Sumanta; Pramanik, Priyanjana; Nanda, Priya; Bhutta, Zulfiqar A.; Afsana, Kaosar; Menon, Purnima
Abstract: Early marriage (EM) and early childbearing (ECB) have far‐reaching consequences. This study describes the prevalence, trends, inequalities, and drivers of EM and ECB in South Asia using eight rounds of Demographic and Health Survey data across 13 years. We report the percentage of ever‐married women aged 20–24 years ( n = 105, 150) married before 18 years (EM) and with a live birth before 20 years (ECB). Relative trends were examined using average annual rate of reduction (AARR). Inequalities were examined by geography, marital household wealth, residence, and education. Sociodemographic drivers of changes for EM were assessed using regression decomposition analyses. We find that EM/ECB are still common in Bangladesh (69%/69%), Nepal (52%/51%), India (41%/39%), and Pakistan (37%/38%), with large subnational variation in most countries. EM has declined fastest in India (AARR of –3.8%/year), Pakistan (–2.8%/year), and Bangladesh (–1.5%/year), but EM elimination by 2030 will not occur at these rates. Equity analyses show that poor, uneducated women in rural areas are disproportionately burdened. Regression decomposition analysis shows that improvements in wealth and education explained 44% (India) to 96% (Nepal) of the actual EM reduction. Investments across multiple sectors are required to understand and address EM and ECB, which are pervasive social determinants of maternal and child wellbeing. Abstract : Early marriage (EM) and early childbearing (ECB) have far‐reaching consequences. This study describes the prevalence, trends, inequalities, and drivers of EM and ECB in South Asia using eight rounds of Demographic and Health Survey data across 13 years.